2008
DOI: 10.1159/000139771
|View full text |Cite
|
Sign up to set email alerts
|

Brain Allopregnanolone in the Fetal and Postnatal Rat in Response to Uteroplacental Insufficiency

Abstract: Background/Aims: Allopregnanolone suppresses central nervous system activity and has neuroprotective actions in hypoxia-induced brain injury. In pregnant sheep allopregnanolone concentrations are high during fetal life and decline rapidly after birth. We investigated brain allopregnanolone concentrations of fetal and postnatal rats derived from normal and growth restricted pregnancies. Methods: Bilateral uterine vessel ligation (or sham) was performed at gestation day 18 to induce uteroplacental insufficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…By 6-7 months of age, there was no difference in body or relative brain weight between the Restricted and Control males. This suggests a degree of accelerated growth but no evidence of brain sparing, 32 neither of which were consistently observed in previous cohorts at 6 months. 12,15 We have previously demonstrated that a poor postnatal lactation environment can be induced by a minor reduction in litter size producing offspring with body weights lower than Controls in early postnatal life.…”
Section: Discussionsupporting
confidence: 73%
“…By 6-7 months of age, there was no difference in body or relative brain weight between the Restricted and Control males. This suggests a degree of accelerated growth but no evidence of brain sparing, 32 neither of which were consistently observed in previous cohorts at 6 months. 12,15 We have previously demonstrated that a poor postnatal lactation environment can be induced by a minor reduction in litter size producing offspring with body weights lower than Controls in early postnatal life.…”
Section: Discussionsupporting
confidence: 73%
“…Both males and females were used for analysis; our model of IUGR leads to a reduced litter size but does not alter the sex ratio of the offspring [33] . As we have previously published [28,33,34] , all offspring from bilateral uterine-vessel ligation litters were considered IUGR; this was confirmed by determining the average pup weight for IUGR versus control litters at P2 (data not shown).…”
Section: Animalsmentioning
confidence: 68%
“…Uteroplacental insufficiency was induced in pregnant rats via bilateral uterine vessel ligation to produce IUGR offspring as previously described [28] . Briefly, on E18, pregnant dams were anesthetized and the uterus was exposed.…”
Section: Surgerymentioning
confidence: 99%
“…Growth restriction is a potent stimulus for neurosteroid synthesis in the fetal brain in late pregnancy. The low concentrations of 3Ǐ,5Ǐ-THP in the growth-restricted postnatal brain suggest a delay in the capacity of the adrenal gland or brain to synthesize pregnane steroids or their precursors and may render the postnatal brain vulnerable to hypoxia-induced injury (Westcott, Hirst, Ciurej, Walker, & Wlodek, 2008). At birth, the 3Ǐ,5Ǐ-THP concentrations in the brain fall markedly, probably due to the loss of placental precursors; however, stressors, including hypoxia and endotoxin-induced inflammation, lift up 3Ǐ,5Ǐ-THP concentrations in the newborn brain.…”
Section: Neuroprotective and Excitotoxic Effects Of 5α/ -Reduced Pregmentioning
confidence: 99%